The authority, office and competence in the canonical legal system - BARRA, RODOLFO CARLOS (Prawo Kanoniczne, 2013)
The publication take the law of the Church as its subject. It consists of eight parts. In the first one, the author presents the Church from a legal and organizational perspective. In particular, he draws the attention to the institutional dimension of the People of God. The second part is devoted to the reflections on the legal system that exists in the Church. Continuing his arguments, the author turns to the present – in the third point - the organization of the Church and offices associated with Her. Then, in the fourth and fifth parts there are included arguments of such concepts as: the authority (el órgano), the office (el oficio), the duty and obligation (el cargo), the task (el munus), the function (el ministerio), the task (el oficio). In the sixth part he divagates on the authority of teaching, sanctifying and governing. In the next, the seventh part, the author attempts to a synthetic presentation of the reality of the office, authority and competence of the Church. The last, eighth part is dedicated to the three ways of understanding of the concept of office (el oficio) in the Canon Law.